Electrospun regenerated silk fibroin is a promising biomaterial for the maintenance of inner ear progenitors in vitro. (February 2022) - Li, Guangfei; Yin, Yanbo; Zhang, Yaopeng; Wu, Jingfang; Sun, Shan
Objective: We sought to determine the biocompatibility of electrospun regenerated silk fibroin (RSF) mats with inner ear progenitors, especially their effect on the differentiation of inner ear progenitors into hair cells. Methods: Neonatal mouse cochleae (n = 20) were collected and digested and allowed to form spheres over several days. Cells digested from the spheres were then seeded onto aligned or random RSF mats, with laminin-coated coverslips serving as controls. The inner ear progenitor cell mortality was examined by TUNEL labeling, and the adhesion of cells to the RSF mats or coverslip was determined by scanning electron microscopy. Finally, the number of hair cells that differentiated from inner ear progenitors was determined by Myosin7a expression. Unpaired Student's t-tests and one-way ANOVA followed by a Dunnett's multiple comparisons test were used in this study ( p < 0.05). Results: After 5 days of culture, the inner ear progenitors had good adhesion to both the aligned and random RSF mats and there was no significant difference in TUNEL + cells between the mats compared to the coverslip ( p > 0.05). After 7 days of in vitro differentiation culture, the percentage of differentiated hair cells on the control, aligned, and random RSF mats was 2.5 ± 0.5%, 2.7 ± 0.4%, and 2.4 ± 0.2%, respectively, and there was no significant difference between Myosin7a + cells on either RSF mat compared to controls ( p > 0.05). Conclusion: The aligned and random RSF mats had excellent biocompatibility with inner ear progenitors and helped the inner ear progenitors maintain their stemness. Our results thus indicate that RSF mats represent a useful scaffold for the development of new strategies for inner ear tissue engineering research.